(untitled) (Research, Society and Development, 2021)
This is a theoretical essay based on Rita Laura Segato’s thesis in the context of gender-based violence suffered by burn victims. For Segato, gender violence is the genesis of all other violence and this impacts not only the victim woman, but also the entire society that surrounds her and, in most cases, opines on their bodies, regulates them and not it attributes the real care that is also expected from any and every society. Three thematic categories were listed in order to contribute to the dialogue of Rita Laura Segato and other authors in the aforementioned context, with a view to the proposed methodology. Thus, the categories were listed, namely: 1. Gender violence against burned women; 2. Gender violence against women and other types of violence; 3. Community control of the female body. Further studies based on women such as Rita Segato are needed when addressing gender-based violence against women.